An overview of economic applications of David Schmeidler's models of decision making under uncertainty - Mukerji, S; Tallon, J (University of Oxford, 2003)
This paper surveys some economic applications of the decision theoretic framework pioneered by David Schmeidler. We have organized the discussion around three themes: financial markets, contractual arrangements and game theory. The first section discusses papers that have contributed to a better understanding of financial market outcomes based on ambiguity aversion. The second section focusses on contractual arrangements and is divided into two sub-sections. The first sub-section reports research on optimal risk sharing arrangements, while in the second sub-section, discusses research on incentive contracts. The third section concentrates on strategic interaction and reviews several papers that have extended different game theoretic solution concepts to settings with ambiguity averse players. A final section deals with several contributions that are linked only at a formal level, in terms of the pure mathematical structures involved, with Schmeidler's models of decision making under ambiguity. The contributions involve issues such as, inequality measurement, intertemporal decision making and multi-attribute choice.